LncRNA Nqo1-AS1 Attenuates Cigarette Smoke-Induced Oxidative Stress by Upregulating its Natural Antisense Transcript Nqo1 - Zhang, Haiyun; Guan, Ruijuan; Zhang, Zili; Li, Defu; Xu, Jingyi; Gong, Yuxin; Chen, Xin; Lu, Wenju (Frontiers in Pharmacology, 2021)
Evidence of the involvement of long noncoding RNAs (lncRNAs) in the pathogenesis of chronic obstructive pulmonary disease (COPD) is growing but still largely unknown. This study aims to explore the expression, functions and molecular mechanisms of Fantom3_F830212L20, a lncRNA that transcribes in an antisense orientation to Nqo1.We name this lncRNA as Nqo1 antisense transcript 1 (Nqo1-AS1). The distribution, expression level and protein coding potential of Nqo1-AS1 were determined. The effects of Nqo1-AS1 on cigarette smoke (CS)-induced oxidative stress were also evaluated. The results showed that Nqo1-AS1 were mainly located in the cytoplasm of mouse alveolar epithelium and had a very low protein coding potential. Nqo1-AS1 (or its human homologue) was increased with the increase of CS exposure. Nqo1-AS1 overexpression enhanced the mRNA and protein levels of Nqo1 and Serpina1 mRNA expression, and attenuated CS-induced oxidative stress, whereas knockdown of Nqo1-AS1 significantly decreased Nqo1 and Serpina1 mRNA expressions, and aggravated CS-induced oxidative stress. Nqo1-AS1 increased Nqo1 mRNA stability and upregulated Nqo1 expression through antisense pairing with Nqo1 3’UTR. In conclusion, these results suggest that Nqo1-AS1 attenuates CS-induced oxidative stress by increasing Nqo1 mRNA stability and upregulating Nqo1 expression, which might serve as a novel approach for the treatment of COPD.